2021
DOI: 10.3390/jcm10051138
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study to Evaluate the Efficacy of Polynucleotide Sodium Compared to Sodium Hyaluronate and Crosslinked Sodium Hyaluronate in Patients with Knee Osteoarthritis

Abstract: Degenerative arthritis of the knee joint has become a major social problem worldwide due to population aging. There are several treatment options for knee osteoarthritis, and the intraarticular injection of sodium hyaluronate is commonly selected by many clinicians as a nonsurgical treatment. However, the efficacy of the treatment is controversial. In this pilot study, we aimed to compare polynucleotide sodium (Conjuran®) with sodium hyaluronate (Hyruan Plus®) and 1,4-butanediol diglycidyl ether-crosslinked so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…It has been reported that PN can be used in a 40 mg/2 mL prefilled syringe and PDRN can be used at 5.625 mg/3 mL (Placentex Inj ® ; Mastelli srl, Sanremo, Italy) [116,122]. The number of uses of PN or PDRN can be once a week to about 3-5 times, like HA [119,124,128]. PDRN/PN has recently been used in knee osteoarthritis compared to HA or CL HA.…”
Section: Pdrn/pn Administration Methods (Frequency Dose)mentioning
confidence: 99%
“…It has been reported that PN can be used in a 40 mg/2 mL prefilled syringe and PDRN can be used at 5.625 mg/3 mL (Placentex Inj ® ; Mastelli srl, Sanremo, Italy) [116,122]. The number of uses of PN or PDRN can be once a week to about 3-5 times, like HA [119,124,128]. PDRN/PN has recently been used in knee osteoarthritis compared to HA or CL HA.…”
Section: Pdrn/pn Administration Methods (Frequency Dose)mentioning
confidence: 99%
“…The performance of Cartistem ® was also compared with microfracture, a method applied successfully for the repair of small cartilage defects and not so successfully for the repair of large cartilage lesions [ 105 ] ( Table 3 ). Apart from Cartistem ® , a limited number of acellular HA-based hydrogels (e.g., Hydros, Hydros-TA [ 106 ], Gel-One ® [ 107 , 108 , 109 , 110 ], HYA-JOINT Plus [ 111 ], hylastan SGL-80 [ 112 ], Cingal ® [ 113 ], Monovisc ® [ 113 , 114 ], Durolane ® [ 115 , 116 , 117 ], XLHA [ 118 ] and Synovian ® [ 119 ]) have also been evaluated in clinical trials regarding their (long-lasting) analgesic efficiency and improvement of physical function in comparison with typical HA-based viscosupplements and corticosteroids in patients with knee OA ( Table 3 ).…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…In this context, Condrotide (20 mg/mL, Mastellisa, Italy), an innovative medical product composed of polynucleotides (PN), has been developed and utilized since 2010 [33][34][35][36][37]. PNs, derived from the milt of salmon or trout, consist of (deoxy)ribonucleotides containing purines and pyrimidines.…”
Section: Introductionmentioning
confidence: 99%